Computer-assisted design and rapid prototype modeling in microvascular mandible reconstruction - Hanasono, Matthew M; Skoracki, Roman J (The Laryngoscope, 2013)
To evaluate the use of computer-assisted design and rapid prototype modeling to improve the speed and accuracy of mandibular reconstruction. Case-control study. Between 2005 and 2011, 38 subjects underwent fibula free flap mandibular reconstruction using computer-assisted design and rapid prototype modeling. Titanium plates were prebent using the models prior to surgery. Direct plate bending on the native mandible to accurately restore occlusion would not have been possible in 11 patients with exophytic tumors, nine patients with pathologic fractures, and 10 patients with a prior segmental mandibulectomy. Computer-generated cutting guides were utilized to facilitate fibular osteotomies. The mean operative time for subjects was 8.8 ± 1.0 hours compared to the mean operative time defect-matched control group, for whom computer-assisted design and models were not used, of 10.5 ± 1.4 hours (P = .0006). Comparison of the preoperative and postoperative mandibles demonstrated that the mean change in position of selected bony landmarks (condyles, gonions, and gnathion) was less in the subject group than in the control group (4.11 ± 3.09 mm vs. 6.92 ± 5.64 mm, respectively; P = .001) Comparison of postoperative mandibles with preoperative virtual plans showed a mean deviation of 2.40 ± 2.06 mm from planned fibular segment lengths and 3.51 ± 2.69° from planned angles between fibular segments. Computer-assisted design and rapid prototype modeling have the potential to increase the speed and accuracy of mandibular reconstruction. We believe these technologies are particularly useful for cases in which the original architecture of the mandible has been distorted or destroyed.